Peningkatan pemahaman penggunaan obat rasional pada anak tingkat sekolah dasar - Fahmi Dimas Abdul Azis; Umi Narsih; Riatul Maulia Hasanah; Nurlita K (Jurnal Dedikasi Masyarakat, 2021)
The problem encountered in society is the use of drugs freely without permission or a doctor's prescription which can cause new health problems. With this service activity, the aim is to increase students' knowledge as participants on how to use rational medicine and realize Gema Cermat at SDN Selogudig Wetan I. The activity is carried out by conducting outreach using a participatory regional assessment model. Participants are invited to get involved and one way is to use the approach of giving prizes to students who are active during the activity. Several stages are carried out, namely problem recognition, problem formulation, problem-solving, and counseling on rational drug use. Counseling uses animated video media and is invited to sing and play to motivate student activities. The material given to participants is the rationality criteria for student drug use. Educational information on rational medical use of drugs and meeting the requirements, namely correct diagnosis, indication of disease, correct drug selection, correct dose, correct method of administration, correct patient, correct information, and alert to side effects. Hasil post-test menunjukkan jika???